Analisa Kualitas Layanan Rumah Sakit Terhadap Kepuasan Pasien : Studi Kasus Rumah Sakit Pemerintah Dan Rumah Sakit Swasta Di Bandar Lampung - Islami, Mouna Sabira Nurul; Marulitua, Rakha Sofyan (Universitas Medan Area, 2024)
Hospitals are health service institutions that serve individuals completely with outpatient, inpatient and emergency care services. As an advanced level of service, hospitals should facilitate patients with adequate services and resources. From data of the Hospital Accreditation Commission (KARS), the largest government-owned hospital in Bandar Lampung still has Accreditation of B. Meanwhile, many private hospitals in the Bandar Lampung area have higher accreditation than the government-owned hospital. Therefore, this research was carried out as a comparative study of government hospital services with private hospitals in Bandar Lampung. This issue was chosen so that evaluations could be carried out regarding services in government hospitals and private hospitals in Bandar Lampung. The method used to measure service quality is the HospitalQuality method with the variables health services (MS), nursing services (NS), support services (SS), administrative services (AS), patient safety (PS), patient communication (PC), hospital infrastructure. (HI), and patient satisfaction (PS). The implementation method is carried out by collecting data, testing data, processing data, testing hypotheses, and interpreting results. Based on t-statistical testing, it is known that the relationship between HospitalQuality dimensions in government hospitals is that the variables AS, NS, and PC have a significant positive relationship with PS, while MS and HI have an insignificant relationship with PS. Different results were obtained in private hospitals where the relationship between the HospitalQuality dimensions MS, NS, AS, PC, and HI had a significant positive relationship with PS.